Ultra-compact tunable fiber laser for coherent anti-Stokes Raman imaging - Gottschall, Thomas; Meyer-Zedler, Tobias; Schmitt, Michael; Huber, Robert; Popp, Jürgen; Tuennermann, Andreas; Limpert, Jens (Journal of Raman Spectroscopy, 2021)
This work describes the construction of an ultra-compact narrowband fiber laser source for coherent anti-Stokes Raman scattering microscopy of Raman tags, that is, for addressing Raman resonances of deuterated molecules and alkyne tags in the spectral range from 2080 to 2220 cm−1. A narrowband and fast electronically tunable cw seed source based on a semiconductor optical amplifier (SOA) emitting around 1335 nm has been employed to seed four-wave mixing (FWM) in an endlessly single mode fiber (ESM) pumped by a ps pulse duration Yb-fiber laser. A conversion efficiency of 50% is demonstrated. This compact fiber optical parametric amplifier (FOPA) has been used to perform coherent anti-Stokes Raman imaging experiments of crystalline deuterated palmitic acid.
CRIS-Team Scopus Importer:2023-04-20
Keywords: coherent anti-Stokes Raman scattering microscopy; four-wave mixing; nonlinear microscopy; ultrafast laser